Our Nations bone health: Prevention and treatment of Cervical hip fracture caused by Osteoporosis - Afa Bayramova (Open Journal of Orthopedics and Rheumatology - Peertechz Publications, 2018)
Fractures that occur against the background of osteoporosis represent a global medical and social problem. In elderly people, 90% of hip fractures, as international studies have shown, occur against the background of osteoporosis. According to WHO, it is the fractures of the proximal femur that put osteoporosis on the 4th place among all causes of disability and mortality.